Perumusan Tatanan Pesantren Rintisan Melalui Siklus 5-D Asset-Based Community Development (ABCD) - Ade Fitriani Harahap; Muhammad Wahyudi Azzukhruf (UIN Sunan Kalijaga, 2026)
Abstract - Emerging pesantren often face institutional challenges in aligning their visionary goals with a well-structured operational system. This study addresses the academic question of how a newly established pesantren can build its institutional foundation from within, without relying on a top-down approach. It analyzes the Majelis Perumusan Tatanan Pesantren program at Pondok Pesantren Bil Qolam, a literacy-based pesantren for university students that aspires to a transformative vision but lacks a formal system. Using a qualitative approach grounded in Asset-Based Community Development (ABCD), this research explores the application of the 5-D cycle (Define, Discovery, Dream, Design, Destiny) as a participatory facilitation method. The findings reveal that this approach successfully transformed the pesantren's internal assets—such as the founder's vision, the students' intellectual capacity, and existing social networks—into tangible institutional instruments, including a curriculum, Standard Operating Procedures (SOP), and a structured daily schedule. The main finding highlights the emergence of an institutional framework that is managerial in structure and aligned with the community's unique character, though ownership of this framework currently remains concentrated among the founder and core administrators rather than fully distributed across the broader santri community. The study concludes that the ABCD method, through the 5-D cycle, serves as an effective framework for developing an authentic institutional foundation in emerging pesantren, while highlighting the need for further efforts to extend collective ownership beyond key actors to ensure long-term sustainability. Keyword: Appreciative Inquiry, Participatory Facilitation, Literacy Education, Emerging Pesantren, 5-D Cycle. Abstrak - Pesantren rintisan seringkali menghadapi permasalahan kelembagaan dalam menyelaraskan visi besarnya dengan sistem operasional yang tertata. Penelitian ini menjawab permasalahan akademik mengenai bagaimana sebuah pesantren baru dapat membangun fondasi kelembagaannya dari dalam, tanpa menggunakan pendekatan yang bersifat top-down. Artikel ini menganalisis program